Moxifloxacin-warfarin interaction - Yan Ji; Youssef Hokayem (Greater Baltimore Medical Center, 2012)
Two case reports presented here show elevated prothrombin time/international normalized ratios (PT/INR) following coadministration of warfarin and moxifloxacin. Although the underlying mechanism of this interaction still remains unclear, health care providers should be careful when prescribing moxifloxacin to patients on warfarin therapy, especially to patients with low albumin levels. More frequent monitoring of INR in these patients may be warranted.